2017
DOI: 10.1515/advgeom-2016-0034
|View full text |Cite
|
Sign up to set email alerts
|

Tight sets in finite classical polar spaces

Abstract: We show that every i-tight set in the Hermitian variety H(2r + 1, q) is a union of pairwise disjoint (2r + 1)-dimensional Baer subgeometries $\text{PG}(2r+1,\,\sqrt{q})$ and generators of H(2r + 1, q), if q ≥ 81 is an odd square and i < (q2/3 − 1)/2. We also show that an i-tight set in the symplectic polar space W(2r + 1, q) is a union of pairwise disjoint generators of W(2r + 1, q), pairs of disjoint r-spaces {Δ, Δ⊥}, and (2r + 1)-dimensional Baer subgeometries. For W(2r + 1, q) with r even, pairs of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Tight sets and intriguing sets in the geometric setting cover a variety of topics of interest to finite geometers, including movoids of generalized quadrangles and Cameron-Liebler classes among others. Intriguing sets, with a focus on tight sets, in (the point graph of) various finite geometries have received a lot of attention in recent years; see for example [1,6,7,11].…”
Section: Introductionmentioning
confidence: 99%
“…Tight sets and intriguing sets in the geometric setting cover a variety of topics of interest to finite geometers, including movoids of generalized quadrangles and Cameron-Liebler classes among others. Intriguing sets, with a focus on tight sets, in (the point graph of) various finite geometries have received a lot of attention in recent years; see for example [1,6,7,11].…”
Section: Introductionmentioning
confidence: 99%
“…Known results on m-ovoids and i-tight sets are surveyed in [5,6]. See [22,26,28,34,78,71] for recent constructions of m-ovoids and i-tight sets.…”
Section: A Generalization Of Semi-primitive Examplesmentioning
confidence: 99%
“…About characterization results, some small i-tight sets of H(2r − 1, q 2 ) are characterized. Nakić and Storme [14] showed that an i-tight set in H(2r − 1, q 2 ), q ≥ 9 odd, must be a union of pairwise disjoint generators of H(2r − 1, q 2 ) and (2r − 1)-dimensional Baer subgeometries PG(2r − 1, q) when i < (q 4/3 − 1)/2. Similar results on small tight sets of H(2r, q 2 ) can be found in [6,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Nakić and Storme [14] showed that an i-tight set in H(2r − 1, q 2 ), q ≥ 9 odd, must be a union of pairwise disjoint generators of H(2r − 1, q 2 ) and (2r − 1)-dimensional Baer subgeometries PG(2r − 1, q) when i < (q 4/3 − 1)/2. Similar results on small tight sets of H(2r, q 2 ) can be found in [6,13,14]. For known constructions of tight sets in H(2r, q 2 ) we refer readers to [1,5,6].…”
Section: Introductionmentioning
confidence: 99%